INTERNALIZATION OF RELIGIOUS MODERATION EDUCATION THROUGH CULTURE LITERACY WITH A NATIONAL INSIGHT - BR, Rosyadi; Mundiri, Akmal; Nuril, Laila; Hina, Shahzadi (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study was to describe the strategies carried out by educators at MAN 1 Probolinggo as superior madrasas in an effort to instill religious moderation values. As well as the implementation of moderation values that were implemented through a literacy culture with a national perspective by educators at MAN 1 Probolinggo towards students. This research used a qualitative approach through case studies. The research was developed through several forms consisting of; integration, indoctrination, democratization and enculturation. The process of data analysis researchers collect data, analyze data. The results of the study showed the success of applying moderation in everyday life through a culture of literacy with a national perspective. So that the benchmark for moderation education was literacy that builds students' critical power, then teacher creativity in class management so that it accommodated the student's critical power and so that teachers indoctrinated religious moderation values in creative and interesting ways according to learners character. The results obtained from this indoctrination were students are able to be tolerant, flexible, not rigid, and open minded.